Królewna Śnieżka i płeć kulturowa (Lustereczko powiedz przecie, kto jest najpiękniejszy w świecie?) - Gromkowska-Melosik, Agnieszka (Wydawnictwo Naukowe UAM, 2018)
The article is devoted to the reconstruction of Snow White myth in contemporary culture in the relation to the changing concepts of femininity and masculinity. The Author takes into account several contexts of this issue. First, it can be understood in the terms of patriarchal power over women’s identity and body. Also, the author analyses the Snow White in a light of girl’s socialization into passive roles. In the article feminist interpretation of Snow White are also reconstructed. The different versions of Snow White fable are confronted with the various kinds of relations between women and men in contemporary society.
Snow White and Gender (Mirror, Mirror on the Wall, Who is the Fairest of Them All?)
Keywords: Snow White; fairy tales; femininity; interpretation; identity